Electrodeposited nickel (and other metal) allergenic effects: some further thoughts. (4th March 2017) - Gabe, D. R.; Larson, C.
Abstract : Nickel, when used as an undercoat for decorative items such as costume jewellery, and even some industrial components in direct and prolonged contact with skin, has been shown to create allergic contact dermatitis (ACD) in sensitised persons. As a result many countries now abide by the EU Nickel Directive limiting migration or release of nickel to skin contact. Other materials have been considered, in bulk alloy and electroplated form, to avoid the onset of nickel allergy but some recent research appears to show that even metals thought of as inert and low risk can display symptoms of allergenic behaviour.